Gender disparity and temporal trend of liver cancer in China from 1990 to 2019 and predictions in a 25-year period - Tingting Yue; Ming Xu; Ting Cai; Haizhen Zhu; Mahmoud Reza Pourkarim; Mahmoud Reza Pourkarim; Mahmoud Reza Pourkarim; Erik De Clercq; Guangdi Li; Guangdi Li (Frontiers Media S.A., 2022)
ObjectiveThis study aims to reveal epidemiological features and trends of liver cancer (LC) in China.MethodsWe retrieved data from the Global Burden of Disease database 2019. Joinpoint regression was used to examine the temporal trend of LC. Future trends of LC were estimated using the Nordpred.ResultsThe incidence, mortality, and disability-standardized life year (DALY) rate of LC declined in China from 1990 to 2019. Among >210,000 LC cases in 2019, the LC incidences were nearly 3.15 times higher in males than in females. LC cases and LC-associated deaths were mostly found among patients aged 65 to 69 years. The proportion of LC attributable to hepatitis B decreased over time, whereas the proportions of LC attributable to hepatitis C, alcohol use, and non-alcoholic steatohepatitis increased modestly from 1990 to 2019. The majority of LC-associated deaths could be traced to four risk factors: smoking (20%), drug use (13.6%), alcohol use (11.7%), and high body mass index (10.1%). Based on the Nordpred prediction, there will be a steady decline in the incidence (39.0%) and mortality (38.3%) of liver cancer over a 25-year period from 2020 to 2044.ConclusionThe disease burden of liver cancer in China has declined over the past 30 years. However, it remains important to control liver cancer among high-risk populations, especially elderly males with obesity, alcohol use, tobacco use, and/or drug abuse.